2013
DOI: 10.1007/s40265-013-0146-8
|View full text |Cite|
|
Sign up to set email alerts
|

Promoting Remyelination in Multiple Sclerosis—Recent Advances

Abstract: We review the current state of knowledge of remyelination in multiple sclerosis (MS), concentrating on advances in the understanding of the pathology and the regenerative response, and we summarise progress on the development of new therapies to enhance remyelination aimed at reducing progressive accumulation of disability in MS. We discuss key target pathways identified in experimental models, as although most identified targets have not yet progressed to the stage of being tested in human clinical trials, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 132 publications
0
36
0
Order By: Relevance
“…While it is not the aim of this review to cover drugs which are in the pre-clinical stages of development, it is nonetheless important to highlight critical pre-clinical research on MS that has led to several promising approaches shown to potentiate mechanisms of tissue recovery (Deshmukh et al, 2013; Mangas et al, 2010; Munzel and Williams, 2013; Van der Walt et al, 2010). Among these, stem cells possess a therapeutic potential that is distinct from that of small molecules and biologics.…”
Section: Therapiesmentioning
confidence: 99%
“…While it is not the aim of this review to cover drugs which are in the pre-clinical stages of development, it is nonetheless important to highlight critical pre-clinical research on MS that has led to several promising approaches shown to potentiate mechanisms of tissue recovery (Deshmukh et al, 2013; Mangas et al, 2010; Munzel and Williams, 2013; Van der Walt et al, 2010). Among these, stem cells possess a therapeutic potential that is distinct from that of small molecules and biologics.…”
Section: Therapiesmentioning
confidence: 99%
“…Evaluation of the integrity of myelin in white matter may be important for the diagnosis and assessment of prognosis in MS. Advanced imaging sequences such as myelin water imaging and magnetization transfer MRI have been used to indirectly assess myelin (Alonso-Oriz et al, 2015), however there is a lack of a robust biomarker for demyelination and remyelination in MS patients (Munzel et al, 2013). It would therefore be a significant achievement to develop and validate an MRI technique for direct imaging of conventionally MR “invisible” myelin and use this to evaluate damage and repair to myelin in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…These cells reside in the perivenous demyelinating lesions which generate distinct inflammatory demyelinated plaques situated within the white matter [25]. MS lesions appear in the white matter inside the visual neuron, basal ganglia, brain stem and spinal cord [26]. White matter cells transmit neural signals from grey matter, where Brain Sci.…”
mentioning
confidence: 99%